Teaching Materials for Dynamic Fluids: An Application of Multimodels to Teach Learners' Problem-solving Ability - Lisa Dwi Yanti; Abdul Salam; Dewi Dewantara; Mazlena Binti Murshed (Universitas Lambung Mangkurat, 2023)
Students' ability to solve physics problems is still relatively low, which triggers research to apply various learning models to the learning process. This research aims to test the effectiveness of multimodels in dynamic fluid material to train students' problem-solving abilities. This research used a quantitative research method, which is a Pre-experiment Design. The research trial subjects were 27 students in class XI MIPA 3 SMA Negeri 10 Banjarmasin. Data collection techniques were seen from measuring multimodel learning outcomes based on pre-test and post-test results. Meanwhile, data analysis techniques were taken descriptively, quantitatively, and qualitatively. Based on research results, multimodel learning has a medium level of effectiveness, so it can be implemented in the learning process. Therefore, this multimodel learning can be used as an alternative for training students' problem-solving abilities.